(untitled) (Journal of Shaheed Suhrawardy Medical College, 2025)
Introduction: Misoprostol is increasingly used to manage early pregnancy loss, including incomplete abortion, blighted ovum, missed abortion, and inevitable abortion during the first trimester. It offers a simple, non-invasive, and widely acceptable alternative to traditional surgical methods. While surgical management reduces hospital stay and overall costs, misoprostol provides an effective, patient-friendly option. Objective: To assess the efficacy and safety of misoprostol for uterine evacuation in early pregnancy loss and compare the results with surgical methods. Materials and Methods: This prospective randomized study was conducted on 30 patients at the Department of Obstetrics and Gynecology, CMH RAMU, Cox’s Bazar, from June 2021 to July 2022. Fifteen patients received misoprostol, and 15 underwent surgical management. Results: Of the 15 women treated with misoprostol, 13 (86%) had complete expulsion within 24 hours, and 14 (90%) within seven days. Treatment failed in 1 patient (6.6%), requiring surgical evacuation. Among responders, 98% were satisfied and stated they would use misoprostol again if needed. Conclusion: Misoprostol is an effective, affordable, and non-invasive alternative to surgery, with a success rate of approximately 90% and manageable side effects. It should be prioritized over surgical methods for eligible patients. J Shaheed Suhrawardy Med Coll 2023; 15(2): 21-24